POWER GENERATION FROM PRESSURE REDUCTION IN THE NATURAL (Journal of Mechanical Engineering, 2011)
Power can be generated from the pressure energy of natural gas along its supply chain at various pressure reduction points by using turbo-expanders.  This technology is being applied in different countries around the world.  This paper attempts to asses the potential of using this technology for Bangladesh.  A number of producing wells and pressure reduction stations are investigated.  It is found that pre-heating before expansion is almost always necessary to avoid hydrate formation.  The power obtainable at the wellheads range from 150-500 kW, and that from pressure reduction stations range from 200 kW to 5 MW.DOI: http://dx.doi.org/10.3329/jme.v41i2.7472